Utilization of Biomimetic Design on the Design of an Internet of Things-Based Smart Air Purifier in Urban Residences - Rahmawati, Hanifah Indah; Meirawan, Danny; Rahayu, Sri; Fauzan, Mochammad Rizal; Azmi, Mutiara Nabila; Fauzi, Rafi Zahran (Jurnal Teknik Sipil dan Lingkungan, 2025)
Poor air quality in urban areas significantly impacts public health, productivity, and quality of life. Various efforts have been made to address this issue, but many solutions still have limitations, such as low effectiveness, designs that lack portability, and the inability for real time monitoring. This research aims to develop a smart air purifier based on biomimetics and the Internet of Things (IoT) as an innovative solution to improve air quality in urban residences. The device prototype mimics the mechanism of leaf stomata, which naturally regulate the flow of air and gases, thus enabling more optimal clean air circulation. The system can monitor environmental parameters, namely temperature, humidity, air pressure, and Indoor Air Quality (IAQ) Index, in real time using BME680 and MQ-135 sensors, and can be controlled via Google Assistant. Testing was conducted in three locations in West Java Province, Indonesia: Cilame, Cibiru, and Jatinangor. Linear regression analysis was used to evaluate the relationship between environmental variables and air quality. The results showed that the device was able to significantly improve air quality in all locations, especially in Cilame, with air pressure being the dominant factor affecting IAQ (coefficient of determination 0.88). Different from previous research, this device offers advantages in the form of high portability, real time monitoring, and IoT integration, making it a potential sustainable solution for improving the air quality of urban residences.